Towards an epistemically neutral curriculum model for vocational education: from competencies to threshold concepts and practices. (1st September 2016) - Hodge, Steven; Atkins, Liz; Simons, Michele
Abstract : Debate about the benefits and problems with competency-based training (CBT) has not paid sufficient attention to the fact that the model satisfies a unique, contemporary demand for cross-occupational curriculum. The adoption of CBT in the UK and Australia, along with at least some of its problems, can be understood in terms of this demand. We argue that a key problem with CBT is that as a cross-occupational curriculum model it impacts too strongly on the way particular occupations are known and represented. Following this line of argument, we propose that more effective models will be those that are 'epistemically neutral' and thus responsive to the inherent knowledge and practice structures of occupations. We explore the 'threshold concepts' approach as an alternative that can claim to be sensitive to occupational structures. We indicate ways it contrasts with CBT but also note some difficulties with the approach for vocational education.